2009
DOI: 10.1017/s0714980809990043
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Acceptability and Feasibility of Conducting a Large Longitudinal Population-Based Study in Canada

Abstract: Successful recruitment and retention for population-based longitudinal studies requires understanding facilitators and barriers to participation. This study explored Canadians' views regarding one such study, the proposed Canadian Longitudinal Study on Aging (CLSA). Focus groups of participants > or =40 years of age were held in six proposed CLSA data collection sites (Halifax, Montreal, Hamilton, Winnipeg, Calgary, and Vancouver) to discuss participating in a long-term study of healthy aging. There was fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…Our results are also consistent with existing knowledge regarding motives for participation in volunteer-based cohorts on health and nutrition, which do not use the Internet [24,26-28]. These reasons for participation may reflect altruistic tendencies, but also a vested personal interest [27].…”
Section: Discussionsupporting
confidence: 89%
“…Our results are also consistent with existing knowledge regarding motives for participation in volunteer-based cohorts on health and nutrition, which do not use the Internet [24,26-28]. These reasons for participation may reflect altruistic tendencies, but also a vested personal interest [27].…”
Section: Discussionsupporting
confidence: 89%
“…The magnitude of the expectation of personal benefit as well as the conflation between research and clinical settings had already been shown in different biobank research settings (in diseasespecific biobanks [19], in pediatric biobanks [22,53]) as well as in studies assessing the hypothetical willingness to participate [27][28][29][30]. However, the magnitude of this expectation in our review is rather unexpected for the type of donors investigated and is, as such, worth further examination.…”
Section: Discussionmentioning
confidence: 49%
“…Similarly, mistrust and consequent concerns about privacy were identified as main barriers to enrollment among hypothetical participants [26]. Many of the potential donors also see participation as a way of 'supplementing their healthcare monitoring' [27] and have explicit expectations regarding the return of individual research results [28][29][30][31].…”
mentioning
confidence: 99%
“…Some factors we found influencing the research participation of adults with ASD are similar to those identified in the literature for neuro-typical people and people with an intellectual disability). The motivators of participation were found to be both social and personal in nature (as reported by Barton et al, 2012;Clark, 2010;Hunter et al, 2012;Kirkland et al, 2009;Mapstone et al, 2007;Mein et al 2012). Travel and time were common inhibitors to participation (e.g., Barton et al, 2012;Beadle-Brown et al, 2012;Bonk, 2010;Brodaty et al, 2013;Marcantonio et al, 2008;Nicholson et al, 2012) while information access (Barton et al, 2012;Hunter et al, 2012;Leonard et al, 2003;Mein et al, 2012) and belonging to a research community Robinson et al, 2007) were enablers of participation.…”
Section: Common Factorsmentioning
confidence: 81%